High‐frequency electrical stimulation suppresses cholinergic accumbens interneurons in acute rat brain slices through GABAB receptors. (23rd September 2014) - Xie, Yijing; Heida, Tjitske; Stegenga, Jan; Zhao, Yan; Moser, Andreas; Tronnier, Volker; Feuerstein, Thomas J.; Hofmann, Ulrich G.
Abstract The nucleus accumbens is selected as a surgical target in deep brain stimulation for treating refractory obsessive‐compulsive disorder (OCD). One of the therapeutic benefits of this procedure is that the abnormal hyper‐functioning prefrontal cortex of patients with OCD is restored during stimulation. One hypothesis regarding the mechanism of deep brain stimulation is that the neuronal electrophysiological properties are directly altered by electrical stimulation; another hypothesis assumes that the stimulation induces selective neuron transmitter release, such as γ‐aminobutyric acid (GABA). In this study, we used multi‐electrode arrays with electrode size of 40 × 40 μm to record electrophysiological signals from the large nucleus accumbens neurons in acute rat brain slices while applying electrical stimulation simultaneously. We revealed that high‐frequency stimulation (HFS, 140 Hz) suppressed the spontaneous neuronal firing rate significantly, whereas low‐frequency stimulation (LFS, 10 Hz) did not. Both HFS and LFS have no effect on neuronal firing pattern or on neuronal oscillation synchrony. GABAB receptor antagonism reversed the HFS‐provoked neuronal inhibition, whereas GABAA receptor blockade failed to affect it. The recorded neurons were pharmacologically identified to be cholinergic interneurons. We propose that HFS has a direct suppressive effect on the identified accumbal acetylcholine (ACh) interneurons by enhancing GABA release in the stimulated region. Potentially, suppressed ACh interneurons decrease the disinhibiting function of medium‐sized spiny neurons in the striato‐thalamo‐cortical circuit. This finding might give an indication of the mechanism of the therapeutic effect of HFS in nucleus accumbens on restoring the abnormal hyperactive prefrontal cortex status in OCD.